Urokinase Antigen in Plasma of Patients with Liver Cirrhosis and Hepatoma - Kirchheimer, J C; Huber, K; Polterauer, P; Binder, B R (Thrombosis and Haemostasis, 1985)
Plasma urokinase antigen levels were studied in 78 patients suffering from liver diseases. Blood was drawn before any specific medication was initiated. Impairment of liver function was comparable in all patients. In both groups of cirrhotic liver disease (alcoholic and non-alcoholic), normal levels of plasma urokinase antigen were found as compared to age-matched control groups. In both groups of patients with hepatomas (with or without a history of liver cirrhosis), however, significantly increased plasma urokinase antigen levels could be determined. These data indicate that an increase in plasma urokinase antigen might rather relate to malignant growth in liver disease than to impaired liver function.
Keywords: Urokinase antigen; Plasma prourokinase; Liver cirrhosis; Hepatoma